Maximizing Strategy: Examining the Key Factors that Shape Customer Satisfaction Through the Use of QRIS Features in the BSI Mobile App - Sari, Nurma; Dhiya Alifa (Fakultas Ekonomi dan Bisnis Islam, 2024)
The purpose of this study is to analyze the influence of knowledge, convenience, and security on customer satisfaction with feature users Quick Response Code Indonesian Standard (QRIS) on the BSI application Mobile. The sample in this study amounted to 100 respondents obtained through the technique purposive sampling. The data used in this study are primary data and secondary data. Primary data was obtained from distributing questionnaires to respondents and secondary data from library research. The analysis used is Multiple Linear Regression. The results showed that partially the knowledge, convenience, and security variables had a significant effect on customer satisfaction using the BSI QRIS feature Mobile. Simultaneously, the knowledge, convenience, and security variables affect customer satisfaction using the BSI QRIS feature Mobile. Therefore, to increase customer satisfaction, service providers can improve functions and provide outreach to customers to maintain customer satisfaction.